PERANAN REFLEKSI GURU DALAM UPAYA MENINGKATKAN MANAJEMEN KELAS [THE ROLE OF TEACHER’S REFLECTION IN EFFORTS TO IMPROVE CLASS MANAGEMENT] - Erikasari, Elisabeth; Agustin, Atalia; Hidayat, Dylmoon (JOHME: Journal of Holistic Mathematics Education, 2021)
Reflective learning is one of the actions in which the teacher observes the shortcomings that occur in the classroom. Reflective learning aims to find solutions to every problem that arises when the teacher teaches, so that class management runs well. This reflection process consists of 4 stages: concrete experience, reflective observation, abstract conceptualization, and active experimentation. The focus of the study in this paper is on Christian education, Christian teachers, students, reflective learning, and classroom management. The method used is analysis based on literature study. Reflective learning practices that rely on the Holy Spirit in the progressive sanctification process to become like God in responding to each student's behavior according to the principles of the Christian faith. Reflective learning is important to be applied in the classroom, because through reflective learning the teacher will be more sensitive to problems in the classroom. Based on the results of this study, it can be said that the difficulties experienced by the author during the reflection process; first, student teachers do not see the importance of assertiveness in leading the class. Second, do not give a firm attitude during the learning process. Third, student teachers are not consistent in carrying out discipline in the classroom. It is recommended that in the implementation of reflective learning, teachers need to have sufficient experience and competence, and need to carry out a complete reflective learning cycle to complete the completion of overcoming the class.BAHASA INDONESIA ABSTRACT: Pembelajaran reflektif adalah salah satu tindakan dimana guru melakukann observasi, terhadap kekurangan yang terjadi dalam kelas. Pembelajaran reflektif bertujuan untuk menemukan solusi untuk setiap permasalahan yang muncul saat guru mengajar, sehingga manajemen kelas berjalan dengan baik. Proses refleksi ini terdiri dari 4 tahap: concrete experience, reflective observation, abstract conceptualization, dan active experiment. Fokus kajian dalam paper ini mengenai pendidikan Kristen, guru Kristen, siswa, pembelajaran reflektif, dan manajemen kelas. Metode yang digunakan adalah analisis berdasarkan studi literature. Praktik pembelajaran reflektif yang mengandalkan Roh Kudus dalam proses progressive sanctification untuk menjadi semakin serupa dengan Allah dalam merespons setiap perilaku siswa sesuai prinsip iman Kriten. Pembelajaran reflektif penting untuk diterapkan dalam kelas, karena melalui pembelajaran reflektif guru akan semakin peka dengan permasalahan dalam kelas. Berdasakan hasil dari penelitian ini dapat disimpulkan bahwa kesulitan yang dialami penulis selama proses refleksi; pertama, mahasiswa guru tidak memandang penting sikap tegas dalam memimpin kelas. Kedua, tidak memberikan sikap tegas selama proses belajar. Ketiga, mahasiswa guru tidak konsisten adalam menjalankan sikap disiplin dalam kelas. Disarankan dalam pelaksanaan pembelarajan reflektif guru perlu memiliki pengalaman dan kompetensi yang cukup, serta perlu melakukan siklus pembelajaran reflektif secara utuh untuk memberikan penyelesaian dalam mengatasi kelas.